The world court : what it is and how it works; - Rosenne, Shabtai (The world court: what it is and how it works, 1989)
As was true for previous editions of this book, the present edition offers the nonspecialist reader: the politician, diplomat, journalist or student of international law and relations - a guide and introduction to the International Court of Justice; what it is and how it works." "This sixth edition utilizes Shabtai Rosenne's original text wherever possible and provides a complete revision of Rosenne's work and updates new material wherever necessary. The step by step explanation of how a case is tried is still based on the Military and Paramilitary Activities in and against Nicaragua case, due to the fact that virtually every procedural situation that exists played a role in that case, as well as to the continuing influence of that case on the role of the Court."--Jacket